Prospects of In vivo Incorporation of Non-canonical Amino Acids for the Chemical Diversification of Antimicrobial Peptides - Baumann, Tobias; Nickling, Jessica H.; Bartholomae, Maike; Buivydas, Andrius; Kuipers, Oscar P.; Budisa, Nediljko (Frontiers in Microbiology, 2017)
The incorporation of noncanonical amino acids is an elegant way for the chemical diversification of recombinantly produced antimicrobial peptides (AMPs). Residue- and site-specific installation methods in several bacterial production hosts hold great promise for the generation of new-to-nature AMPs, and can contribute to tackle the ongoing emergence of antibiotic resistance in pathogens. Especially from a pharmacological point of view, desirable improvements span pH and protease resistance, solubility, oral availability and circulation half-life. Although the primary focus of this report is on ribosomally synthesized and post-translationally modified peptides (RiPPs), we have included selected cases of peptides produced by solid phase peptide synthesis to comparatively show the potential and impact of ncAA introduction. Generally speaking, the introduction of ncAAs in recombinant AMPs delivers novel levels of chemical diversification. Cotranslationally incorporated, they can take part in AMP biogenesis either through direction interaction with elements of the post-translational modification (PTM) machinery or as untargeted sites with unique physicochemical properties and chemical handles for further modification. Together with genetic libraries, genome mining and processing by PTM machineries, ncAAs present not a mere addition to this process, but a highly diverse pool of building blocks to significantly broaden the chemical space of this valuable class of molecules. This perspective summarizes new developments of noncanonical amino acid containing peptides. Challenges to be resolved in order to reach large-scale pharmaceutical production of these promising compounds and prospects for future developments are discussed.